A physics-based algorithm for the estimation of bearing spall width using vibrations. (1st May 2018) - Kogan, G.; Klein, R.; Bortman, J.
Highlights: An autonomous tool for estimation of the spall width in rolling element bearings. The algorithm is based on insights from a dynamic model of ball bearings. The parameters are derived from an analysis of the rolling element-spall interaction. The algorithm was validated with experimental data. Abstract: Evaluation of the damage severity in a mechanical system is required for the assessment of its remaining useful life. In rotating machines, bearings are crucial components. Hence, the estimation of the size of spalls in bearings is important for prognostics of the remaining useful life. Recently, this topic has been extensively studied and many of the methods used for the estimation of spall size are based on the analysis of vibrations. A new tool is proposed in the current study for the estimation of the spall width on the outer ring raceway of a rolling element bearing. The understanding and analysis of the dynamics of the rolling element-spall interaction enabled the development of a generic and autonomous algorithm. The algorithm is generic in the sense that it does not require any human interference to make adjustments for each case. All of the algorithm's parameters are defined by analytical expressions describing the dynamics of the system. The required conditions, such as sampling rate, spall width and depth, defining the feasible region of such algorithms, are analyzed in the paper. The algorithm performance was demonstrated with experimental data for different spall widths.